Patrones númericos y su relación con la resolución de problemas matemáticos en estudiantes del quinto ciclo de primaria en la institución educativa N° 60520 Miguel Grau Seminario, Nauta 2024 - Tuesta Shapiama, Rene (2025)
This study investigated the relationship between numerical pattern recognition and mathematical problem solving in fifth-cycle students. The results showed a very high positive correlation (Spearman's Rho = 0.942**; p < 0.01), suggesting that improving skills in numerical patterns also strengthens the ability to solve mathematical problems. With a non-experimental descriptive-correlational design and quantitative approach, it was found that both variables are closely related. The population consisted of 105 students, who also constituted the study sample. As a data collection technique, a developmental test was applied, using specific questionnaires for both variables.